O apagamento da vogal alta anterior pretônica em sequências [si].C - Amanda Fernandes Ivo (2021)
This dissertation aims at investigating pretonic high vowel [i] deletion in [si].C sequences in Brazilian Portuguese (PB) spoken in city of Belo Horizonte. This deletion may trigger consonant clusters, in words as antecipada > ante[si.p]ada ~ ante[s.p]ada. The investigation of emergent consonant clusters was performed by comparing them with other consonant clusters in BP, e.g. espaçada > e[s.p]açada. Previous studies reported high front vowel weakening in BP when [i] is adjacent with [s]. (BISOL; HORA, 1993; LEITE, 2006; MENESES, 2012; SOUZA, 2012; FREITAS, 2019). However these studies have not considered the vowel [i] preceded by [s] and followed by stop consonant in the following syllable, i.e antecipada > ante[si.p]ada ~ ante[s.p]ada. Moreover, studies about emerging consonant clusters composed by [s] + stop consonant have not been reported. Therefore, this study contributes with the investigation of front the vowel weakening and consonante clusters in BP. Our methodology is based on Laboratory Phonology approaches (PIERREHUMBERT, BECKMAN, LADD, 2000). 16 speakers were recorded and the data were acoustically analyzed. The adopted theoretical approach is Exemplar Theory (JOHNSON, 1997; PIERREHUMBERT, 2001). Results show that vowel deletion is an emergent phenomenon and occurs in 33.3% of the data. Moreover, though both cosonant clusters can be phonetically transcribed as [s].C, they manifest acoustic differences, such as segmental duration. These results indicate that experimental analysis may contribuite to the understanding of the evolution of phonological phenomena. Moreover, the results corroborate the assumptions of Exemplar Theory regarding the incorporation of phonetic detail in phonological representations.